Miniaturized Devices for Isothermal Amplification and Photometric Quantification of Pseudomonas Aeruginosa - P Ramya Priya; Satish Kumar Dubey; Sanket Goel (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: This study introduced a proof-of-concept prototype for isothermal recombinase polymerase amplification (RPA) with miniaturized photometric detection, enabling rapid P. aeruginosa detection. Methods: The researchers conducted the amplification process within a microchamber with a diameter of 10 mm, utilizing a standalone Thermostat driven thermal management setup. RPA, an amplification technique was employed, which required a lower operating temperature of 37 °C–40 °C to complete the reaction. The amplified amplicon was labeled with a fluorophore reporter, stimulated by an LED light source, and detected in real-time using a photodiode. Results: The developed prototype successfully demonstrated the rapid detection of P. aeruginosa using the RPA assay. The process only required the utilization of 0.04 ng of working concentration of DNA. The entire process, from amplification to detection, could be completed in over 15 minutes. The platform showed enhanced sensitivity and specificity, providing a cost-effective and accurate solution for on-site detection/quantification of pathogens. Conclusions: The integration of isothermal RPA with the miniaturized photometric detection platform proved successful in achieving the goal of rapid and specific pathogen detection. This study proved the benefits of Isothermal Nucleic Acid Amplification Technology (INAAT), emphasizing its potential as an accessible, user-friendly point-of-care technology for resource-constrained institutions. The RPA-based prototype demonstrated capability without requiring costly laboratory equipment or expertise. The developed platform, when combined with Internet of Things (IoT) enabled cloud platform, also allowed remote monitoring of data. Overall, the methodology presented in this study offered a cost-effective, accurate, and convenient solution for on-site testing in resource-limited settings.